The Honeys - La Sala, Ryan (Push, 2022)
After his twin sister Caroline dies under horrific circumstances, Mars takes her place at the elite Aspen Conservancy Summer Academy where he finds himself hunted by something toying with his mind that leads him to the Honeys, a group of beautiful--and terrifying--girls.